2016
DOI: 10.1111/ajgw.12212
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of ripening via antitranspirants in cv. Barbera (Vitis vinifera L.)

Abstract: Background and Aims Accelerated berry sugar accumulation resulting in wines of excessive alcohol concentration, sub‐optimal colour and atypical flavour has become increasingly frequent in warm growing districts, a trend induced by factors that include global warming. The application of a film‐forming antitranspirant may be an effective way of reducing early sugar accumulation without affecting colour development. Methods and Results An antitranspirant emulsion was applied in 2013 and in 2014 on field‐grown cv.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
5
20
0
Order By: Relevance
“…Several authors have previously shown that the reduction of leaves with high photosynthetic activity immediately after veraison has no influence on the concentration of anthocyanins and tannins in berries and our results at harvest during the three years confirm these findings. A recent work reported that the strong reduction in leaf‐to‐fruit ratio (from 1.15 to 0.33 m 2 kg −1 caused by the removal of 80% of leaf area) at veraison resulted in a decrease in soluble solid accumulation associated with a significant reduction in secondary metabolites, such as anthocyanins, without substantial differences in their composition.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several authors have previously shown that the reduction of leaves with high photosynthetic activity immediately after veraison has no influence on the concentration of anthocyanins and tannins in berries and our results at harvest during the three years confirm these findings. A recent work reported that the strong reduction in leaf‐to‐fruit ratio (from 1.15 to 0.33 m 2 kg −1 caused by the removal of 80% of leaf area) at veraison resulted in a decrease in soluble solid accumulation associated with a significant reduction in secondary metabolites, such as anthocyanins, without substantial differences in their composition.…”
Section: Discussionsupporting
confidence: 91%
“…Different vineyard strategies are now available to slow down sugar accumulation and decelerate overly quick and unbalanced berry ripening . The most effective of these are based the limitation of substrate availability during ripening through post‐veraison leaf removal of the upper part of the shoots .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, berry traits like weight (BE_We), length (BE_Le), figure online) width (BE_Wi), elongation (BE_E) and shape (BE_SH) were highly correlated, and so happened with some cluster traits like length (CL_L), width (CL_Wi), elongation (CL_E), volume (CL_TV) and weight (CL_We). As observed in different grapevine cultivars (Gatti et al 2016;Ivorra et al 2015), the objective compactness index CI-12 proposed by Tello and Ibáñez (2014) correlated significantly with the visual OIV rating in our sample, supporting the usefulness of this indicator for the quantitative estimation of this trait. Interestingly, seed number (BE_SB) did not correlate significantly with berry dimension variables (BE_We, BE_Wi) or its value of significant correlation was low (BE_Le).…”
Section: Resultssupporting
confidence: 84%
“…Leaf photosynthetic activity can be also interrupted by alternative and innovative systems, including the use of leaf anti‐transpirants and artificial shading. Oily substances used as leaf anti‐transpirants, such as paraffin and pinus oils, occlude the stomata of leaves, hinder their transpiration and influence carbon dioxide absorption, which ultimately hamper the photosynthetic activity of leaves (Palliotti et al , Hanni et al , Gatti et al ). Their application at pre‐flowering and full‐flowering reduces the mobilisation of carbohydrates to developing inflorescences, which promotes flower drop and reduces berry number and bunch compactness (Table ).…”
Section: Which Factors Affect Bunch Compactness?mentioning
confidence: 99%